Digitalne strukture in sistemi: Laboratorijske vaje - Donaj, Gregor (2023)
Digital structures and systems: Laboratory excercises. This material contains the instructions for laboratory work in the subject Digital Structures and Systems for students of the university study program Electrical Engineering, module Electronics. The instructions cover the first steps in using hardware description languages and programmable logic devices. The instructions can also be used for other subjects with a similar syllabus. The instructions cover the implementation of simple combinatorial circuits, the implementation of simple sequential circuits, the simulation of digital circuits, and examples of somewhat more complex useful circuits. In these examples, other topics are covered, such as the interconnection of digital modules, the use of logic analyzers, and a more detailed analysis of the described circuits.
Keywords: electronics; programmable logic device; Verilog; digital circuit simulation; exercises